Rhingia nigra and Eumerus obliquus (Diptera: Syrphidae): first records in Argentina, and comments on range expansion of Eumerus strigatus - Torretta, Juan Pablo (2023)
Two species of syrphid flies are reported for the first time in Argentina: the neotropical Rhingia nigra Macquart and exotic Eumerus obliquus (Fabricius). Individuals of both species were captured in the province of Misiones. Moreover, another individual of E. obliquus was reared from a decaying stem of Austrocylindropuntia subulata (Cactaceae) in the province of Tucumán. Finally, we report the presence of Eumerus strigatus (Fallén) in the province of Chubut, more than 400 km to southwest from its southernmost record.